Contribution of Spartina maritima to the reduction of eutrophication in estuarine systems - Sousa, Ana I. (2008)
http://www.sciencedirect.com/science/article/B6VB5-4T4WM2P-1/2/39c53246a441c97ea5fb560b5d7dd93a